Research on Online Shopping Return Mode in "New Retail" Era. Issue 1 (June 2020) - Zhang, Shubin; Zhong, Fachun; Zhang, Jingjun; Du, Dandan; Zhao, Yuhan; Yuan, Miaomiao
Abstract: Through B2C/C2C platform, online shopping has realized the simplified mode of factory—retailer—consumer. With the rapid development of online shopping and retail industry, consumers' requirements for online shopping and retail services are gradually raising. At present, the size of the new retail market is only 38.94 billion yuan, while as the formation of user habits and the innovation of new retail mode, there is great potential for future growth. It is estimated that the total market size will reach 1.8 billion yuan in 2022. This article analyzes the reasons and existing problems of online shopping return in the "new retail" era, analyzes the logistics modes of online shopping return, self-run shopping return, the third-party return and the alliance return. This paper adopts the method of empirical research to analyze the return of online shopping.